Questions Formation in Musey - Brahim Adam (RIRAI Publisher, 2022)
This article is interested in questions formation in Musey, a chadic language spoken in Chad and Cameroon. It comes within the competence of generative grammar. Kayne’s (1994) Antisymmetry and Rizzi’s (1997, 2001b) Split-CP are used for analyzing the Musey data. Musey is made up of arguments (nge (who) and mege (what)), referential adjuncts (saba (when), aige (where)) and non-referential adjuncts (an mege (how); kai mege (why)). They are focalized à la clause final comp and à la clause initial comp. Since the focus marker ni precedes focused arguments and adjuncts, they are hosted by Spec-FocP. In yes/no questions, the question marker su ends the structures and is hosted by IntP. In embedded questions, the lexical complementizer ana (that) is hosted by ForceP. This study leads to the following projections hierarchy: Int > Cleft > Foc > Force > Agr.